2003
DOI: 10.1111/j.1553-2712.2003.tb00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment for Deaths in Out-of-hospital Heroin Overdose Patients Treated with Naloxone Who Refuse Transport

Abstract: Giving naloxone to patients with heroin overdoses in the field and then allowing them to sign out AMA resulted in no identifiable deaths within this study population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 12 publications
0
39
0
1
Order By: Relevance
“…Two publications report on the medical examiner records of overdose deaths [Vilke et al 1999[Vilke et al , 2003] over a 1-year and 5-year period, respectively. These studies each compare databases of patients who received naloxone for opioid overdose and then left AMA to the databases of the medical examiner for deaths within 12 hours of the naloxone treatment.…”
Section: Post-treatment Recurrence Of Respiratory Depressionmentioning
confidence: 99%
“…Two publications report on the medical examiner records of overdose deaths [Vilke et al 1999[Vilke et al , 2003] over a 1-year and 5-year period, respectively. These studies each compare databases of patients who received naloxone for opioid overdose and then left AMA to the databases of the medical examiner for deaths within 12 hours of the naloxone treatment.…”
Section: Post-treatment Recurrence Of Respiratory Depressionmentioning
confidence: 99%
“…Within 0 to 2 days of naloxone administration, the proportion of patients was 0 percent in three studies [71][72][73] (n=317, 552, and 998), one study 74 reporting one death (0.49% [1/205]), and one study 70 reporting 14 deaths (0.6% [14/2241]): three attributed to likely rebound overdose (0.13%), ten to new overdose, and one to a natural death. The final study reported one case of a life-threatening adverse event (1.2% [1/84]).…”
Section: Detailed Synthesismentioning
confidence: 99%
“…Although six studies reported low rates (0 to 1.2%) of death or serious adverse events among patients who received naloxone for opioid overdose and were not transported to a health care facility, [69][70][71][72][73][74] there was no comparison group of patients who were transported, and the studies provided limited details regarding the characteristics of the nontransported patients. This makes interpretation of findings difficult, as patients who refuse transport or are assessed as not requiring transport are likely to be at lower risk of opioid overdose-related complications than patients who are transported.…”
Section: Key Findings and Strength Of Evidencementioning
confidence: 99%
“…To the Editor:-We read with interest the article by Vilke et al 1 There are several points that we feel require clarification before we would consider allowing narcotic-reversed patients to sign out against medical advice (AMA).…”
Section: Leaving Against Medical Advice After Out-of-hospital Naloxonmentioning
confidence: 99%